GAYA BELAJAR DAN METODE MENGAJAR DOSEN AKUNTANSI - Sri Pujiningsih (JURNAL PENDIDIKAN AKUNTANSI, 2014)
The objectives of this research are to describe learning style and instructional method of accounting lecturers. The subjects of the research are 22 accounting lecturers. Data analysis uses descriptive analysis. Results of the research conclude major of the accounting lecturers have accommodator style.Â  Their learning style influence their instructional method. TheyÂ  prefer give more individual and group assignments.